2012
DOI: 10.1371/journal.pone.0047102
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Foxp3+ Regulatory T Cells during Allergen Provocation Does Not Exacerbate Murine Allergic Airway Inflammation

Abstract: Regulatory T cells (Tregs) play a non-redundant role in maintenance of immune homeostasis. This is achieved by suppressing both, priming of naïve cells and effector cell functions. Although Tregs have been implicated in modulating allergic immune responses, their influence on distinct phases of development of allergies remains unclear. In this study, by using bacterial artificial chromosome (BAC)-transgenic Foxp3-DTR (DEREG) mice we demonstrate that the absence of Foxp3+ Tregs during the allergen challenge sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
16
2
Order By: Relevance
“…The role of Treg cells during allergen-induced airway inflammation has previously been examined. Utilizing BAC-transgenic Foxp3.DTR (DEREG) mice, Baru et al reported that the lack of Treg cells during ovalbumin antigen challenge does not aggravate allergic airway inflammation (25). We tested the roles of Treg cells during CA-induced eosinophilic inflammation using Foxp3.DTR knockin mice (26).…”
Section: Resultsmentioning
confidence: 99%
“…The role of Treg cells during allergen-induced airway inflammation has previously been examined. Utilizing BAC-transgenic Foxp3.DTR (DEREG) mice, Baru et al reported that the lack of Treg cells during ovalbumin antigen challenge does not aggravate allergic airway inflammation (25). We tested the roles of Treg cells during CA-induced eosinophilic inflammation using Foxp3.DTR knockin mice (26).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, depletion of Treg cells can be achieved by DT application [51]. As shown elsewhere [32,56] in naïve DEREG mice a subset of FoxP3 + Treg cells lacking the DT receptor and GFP expression is not affected by the treatment. However, for the infection model described here even a few days of almost total ablation of Treg cells leads to a significant alteration of the immune response.…”
mentioning
confidence: 80%
“…These results are in accordance with our own findings. Furthermore, depletion of Tregs during the sensitization phase can aggravate allergic airway inflammation (Baru et al, 2010), whereas depletion during the challenge phase has no such effect (Baru et al, 2012). Similarly, we could retrace these findings in our own depletion experiments: immunoglobulin responses toward the primary antigen (OVA) were not influenced by depletion of Tregs during the challenge phase (Supplementary Figure S3 online), but depletion of Tregs during EC sensitization with the secondary antigen allowed collateral priming to take place in the skin.…”
Section: Discussionmentioning
confidence: 63%